مساهمة الوسائط الجديدة في تعزيز التدريب الرياضي - خليفي, فاطمة الزهراء; حاج علي, عبد الحميد (كلية العلوم الاجتماعية, 2025)
تهدف هذه الدراسة إلى معرفة دور الوسائط الجديدة في تعزيز التدريب الرياضي. وذلك من خلال القيام بدراسة ميدانية لمدربي الجودو لولاية مستغانم ، و قد اعتمدنا على منهج دراسة حالة، حيث شملت الدراسة على عينة قصدية ،بلغ عددها 5مدربين تم تجميع إجاباتهم من خلال المقابلة التي كانت الأداة الرئيسية التي استخدمت في جمع البيانات و بعد معالجتها توصلنا إلى مجموعة من النتائج أهمها: مساهمة الوسائط الجديدة في تعزيز التدريب الرياضي حيث يعد استخدامها دور فعال في تحسين و تسهيل و رفع المهارة و الأداء عند اللاعبين . إضافة إلى تطلع الجمعيات الرياضية لتطوير و تفعيل دور الوسائط الجديدة و تعميمها من أجل زيادة الكفاءة و فعالية وجود أداء للمدربين. This study aims to determine the role of new media in enhancing sports training. This was done through a field study of judo coaches in the state of Mostaganem. We relied on a case study approach, which included a purposive sample of of five coaches. Their responses were collected through interviews, which were the main tool used to collect data. After processing the data, we arrived at a set of results, the most important of which are: The contribution of new media to enhancing sports training, as its use plays an effective role in improving, facilitating, and raising the skills and performance of players. In addition, sports associations aspire to develop and activate the role of new media and disseminate it in order to increase the efficiency and effectiveness of coaches' performance.
دراسة ميدانية لمدربي الجودو لولاية مستغانم
Keywords: مساهمة ، الوسائط الجديدة ، تطوير ، التدريب الرياضي